TWEAK and the progression of renal disease: clinical translation. (February 2014) - Sanz, Ana B.; Izquierdo, M. Concepcion; Sanchez-Niño, Maria Dolores; Ucero, Alvaro C.; Egido, Jesus; Ruiz-Ortega, Marta; Ramos, Adrián Mario; Putterman, Chaim; Ortiz, Alberto
Abstract : Tumour necrosis factor-like weak inducer of apoptosis (TWEAK) activates the fibroblast growth factor-inducible-14 (Fn14) receptor. TWEAK has actions on intrinsic kidney cells and on inflammatory cells of potential pathophysiological relevance. The effects of TWEAK in tubular cells have been explored in most detail. In cultured murine tubular cells TWEAK induces the expression of inflammatory cytokines, downregulates the expression of Klotho, is mitogenic, and in the presence of sensitizing agents promotes apoptosis. Similar actions were observed on glomerular mesangial cells. In vivo TWEAK actions on healthy kidneys mimic cell culture observations. Increased expression of TWEAK and Fn14 was reported in human and experimental acute and chronic kidney injury. The role of TWEAK/Fn14 in kidney injury has been demonstrated in non-inflammatory compensatory renal growth, acute kidney injury and chronic kidney disease of immune and non-immune origin, including hyperlipidaemic nephropathy, lupus nephritis (LN) and anti-GBM nephritis. The nephroprotective effect of TWEAK or Fn14 targeting in immune-mediated kidney injury is the result of protection from TWEAK-induced injury of renal intrinsic cells, not from interference with the immune response. A phase I dose-ranging clinical trial demonstrated the safety of anti-TWEAK antibodies in humans. A phase II randomized placebo-controlled clinical trial exploring the efficacy, safety and tolerability of neutralizing anti-TWEAK antibodies as a tissue protection strategy in LN is ongoing. The eventual success of this trial may expand the range of kidney diseases in which TWEAK targeting should be explored.